Profiling the Virulence and Antibiotic Resistance Genes of Cronobacter sakazakii Strains Isolated From Powdered and Dairy Formulas by Whole-Genome Sequencing - Parra-Flores, Julio; Holý, Ondrej; Riffo, Francisca; Lepuschitz, Sarah; Maury-Sintjago, Eduard; Rodríguez-Fernández, Alejandra; Cruz-Córdova, Ariadnna; Xicohtencatl-Cortes, Juan; Mancilla-Rojano, Jetsi; Troncoso, Miriam; Figueroa, Guillermo; Ruppitsch, Werner; et al. (Frontiers in Microbiology, 2021)
Cronobacter sakazakii is an enteropathogen that causes neonatal meningitis, septicemia, and necrotizing enteritis in preterm infants and newborns with a mortality rate of 40% to 80%. Powdered and dairy formulas (P-DF) have been implicated as transmission vehicles and the presence of this pathogen in P-DF led to product recalls in Chile in 2017. The objective of this study was to evaluate the profile, virulence, and gene resistance to antibiotics of presumptive C. sakazakii strains previously isolated from P-DF. The strains were re-identified by MALDI-TOF-MS and by whole genome sequencing (WGS). The in vitro detection of virulence genes was evaluated using PCR probes and adherence and invasion ability assays using the Mouse Neuroblastoma N1E-115 cell line. Antibiotic resistance profiles were determined using the disk diffusion method. In silico, plasmids, the virulence and resistant genes were detected using RidomSeqSphere+, PlasmidFinder, Comprehensive Antibiotic Resistance Database platform, and AMRFinderPlus. The CRISPR-cas system was searched with CRISPRCasFinder. Average Nucleotide Identity (ANI), ribosomal MLST and core genome MLST identified seven strains as C. sakazakii and one strain as Franconibacter helveticus. All C. sakazakii strains exhibited adherence, however, only 50% were able to invade. The C. sakazakii strains were positive for six virulence factors. The inv gene was identified in the genome of all C. sakazakii strains, despite being negative using PCR probes. Thirty-one virulence genes were detected by WGS; these were grouped as flagellar proteins, outer membrane proteins, chemotaxis, hemolysins, invasion, plasminogen activator, colonization, transcriptional regulator, survival in macrophages, and the use of sialic acid and toxin genes. Five strains were resistant to cephalothin, four to ampicillin, and two strains to ceftazidime and amoxicillin/clavulanic acid. We detected the mcr-9.1 and blaCSA genes conferring resistance to colistin and cephalothin, respectively. In addition, isolates carried the IncFII(pECLA), Col440I, and Col(pHHAD28) plasmids. All C. sakazakii strains showed CRISPR matrices and three strains had two type I-E and I-F matrices. The use of WGS led to the identification of C. sakazakii and determination of multiple antibiotic resistance and virulence genes. These findings support the decision to recall all the powdered and dairy formulas involved in Chile in 2017.